Bacterial Synergism in Breast Necrotizing Fasciitis: A Case Report on Diagnostic Dilemmas, Therapeutic Challenges, and Reconstructive Management - Leila Essid; Leslie Ann See; Georges Tarris; Narcisse Zwetyenga; Vivien Moris (Case Reports in Infectious Diseases)
Conclusion: Breast NF requires rapid diagnosis and aggressive multidisciplinary management. This case illustrates the need for increased awareness to reduce diagnostic delays and improve survival and reconstructive outcomes.